From corpus to classroom language use and language teaching - O'Keeffe, Anne 1968- (Cambridge University Press, 2007)
From Corpus to Classroom summarises and makes accessible recent work in corpus research, focusing particularly on spoken data. It is based on analysis of corpora such as CANCODE and Cambridge International Corpus, and written with particular reference to the development of corpus-informed pedagogy. The book explains how corpora can be designed and used, and focuses on what they tell us about language teaching. It examines the relevance of corpora to materials writers, course designers and language teachers and considers the needs of the learner in relation to authentic data. It shows how the answers to key questions such as 'Is there a basic, everyday vocabulary for English?', 'How should idioms be taught?' and 'What are the most common spoken language chunks?' are best explored by means of a clearer understanding of the workings of language in context
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Englisch; English language / Study and teaching / Foreign speakers; English language / Spoken English / Study and teaching; English language / Usage / Study and teaching; Corpora (Linguistics); Sprachunterricht; Korpus -- Linguistik